2022
DOI: 10.1186/s12951-022-01248-5
|View full text |Cite
|
Sign up to set email alerts
|

Biomimetic manganese-eumelanin nanocomposites for combined hyperthermia-immunotherapy against prostate cancer

Abstract: Pro-tumoral and immunosuppressive M2-like tumor-associated macrophages (TAMs) contribute to tumor progression, recurrence and distal metastasis. However, current TAMs-modulating therapeutic strategies often encounter challenges including insufficient immune activation, weak antigen presentation ability and unsatisfactory antitumor immune performance. Herein, cyclic RGD peptide functionalized and manganese doped eumelanin-like nanocomposites (RMnMels) are reported for combined hyperthermia-immunotherapy against… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 45 publications
1
7
0
Order By: Relevance
“…Macrophages are polarized by the stimulation of transcription factors in the tumor microenvironment by controlling their antitumor activity and by affecting their immunotherapy [ 23 , 24 ]. Our previous study also confirmed that changes in macrophage polarization play substantial activities to regulate the inflammatory traumatic urethral stricture [ 25 ] and resistance to chemotherapy and endocrine therapy in advanced prostate cancer [ 26 ]. In general, TCF family genes significantly influence the immune system and the state of tumor tissue.…”
Section: Introductionsupporting
confidence: 75%
See 1 more Smart Citation
“…Macrophages are polarized by the stimulation of transcription factors in the tumor microenvironment by controlling their antitumor activity and by affecting their immunotherapy [ 23 , 24 ]. Our previous study also confirmed that changes in macrophage polarization play substantial activities to regulate the inflammatory traumatic urethral stricture [ 25 ] and resistance to chemotherapy and endocrine therapy in advanced prostate cancer [ 26 ]. In general, TCF family genes significantly influence the immune system and the state of tumor tissue.…”
Section: Introductionsupporting
confidence: 75%
“…Another study recently reported that M2-tumor-associated macrophages (TAMs) were able to promote the process of bone metastasis and were able to influence the chemotherapy and drug resistance ability of the cells of prostate cancer. The regulation of the process of macrophage polarization can influence the effect of immunotherapy in patients suffering from prostate cancer [ 26 ]. Sen, Yang GH, and Mondal reported that TCF19, a novel pancreatic islet regulator, regulated the processes of energy metabolism and stress adaptation associated with the tumor cells by regulating gluconeogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Photothermal-induced ICD effect can cooperate with the immune stimulation of Mn 2+ to jointly change TME and improve the therapeutic effect of cancer. 147 PTT ablates tumor cells by local heating. However, this may cause damage to adjacent normal tissues.…”
Section: Immunotherapy Combined With Photothermal Therapymentioning
confidence: 99%
“…Along with these fascinating features, MelNPs also exhibit excellent metal ion chelating ability for high binding affinity toward various paramagnetic metal ions, such as iron, manganese, and gadolinium, as MR contrast agents. [17,22] By doing so in vivo distribution and targeting ability of nanoparticles in lesions could be monitored dynamically. In addition, targeted molecules are integrated to the surface of MelNPs by conjugating with abundant functional groups, such as angiopep-2.…”
Section: Introductionmentioning
confidence: 99%